LESS IS MORE? ON THE NUMBER OF JUDGES AND JUDICIAL EFFICIENCY - Spaić, Bojan; Đorđević, Mila (Pravni zapisi, 2022)
In this paper, we deal with the relationship between the relative number of judges within a jurisdiction and the efficiency of the judiciary. To determine how the number of judges influences efficiency, we compare data on the judiciary from six countries: Serbia, Croatia, Slovenia, France, Austria and Norway. The analysis is based on data collected within the 2020 Evaluation cycle (2018 data) of CEPEJ and World Justice Report Rule of Law Index for 2018. We conclude that judicial efficiency does not increase with an increase in the number of judges in a jurisdiction.
Keywords: judiciary; judicial system; judicial efficiency; judicial organisation; number of judges